Variations and Arguments of Anti-Vaccine Movement Groups on Facebook - Widyaningrum, Novi; Trisnantoro, Laksono; Kurniawan, Nanang Indra (KnE Social Sciences, 2022)
This study examined a social movement in the digitalized world along with its role in the public policy process. The research focused on how the social movement was accessed and spread, and how knowledge was formed on Facebook so that it could influence the success or failure of a certain policy. It is essential to further explore how knowledge is mobilized through social movements in the digitalized world so as to enrich the theories of governance and public policies. In this study, content analysis was ued. The results showed that the group of main actors who criticized the vaccine’s safety was heterogeneous. In terms of vaccine criticism, there were the anti-vaccine movements, the marginally anti-vaccine movements, and the occasionally vaccine-critical movements. This heterogeneity could be found in the type of arguments mobilized to question the vaccine’s safety and in these actors’ likelihood of being involved in any vaccine-related controversies. The religion and conspiracy theory discourses were the two most used discourses to reject the vaccine delivery program in Indonesia. By mobilizing knowledge through a social movement in the digitalized world, the anti-vaccine movement actors had a wider network and had the potential to influence the success of the government program. Keywords: social movement, anti-vaccine, health policy, social media